Laubuka parafasciata, a new cyprinid fish species (Teleostei: Cyprinidae) from Mizoram northeastern India - Lalramliana, Lalramliana; Vanlalhlimpuia, Denis; Singh, Mahender (Zootaxa, 2017)
Laubuka parafasciata, new species, is described from the Sala River of Mizoram, northeast India. The species differs markedly from all its congeners, with the exception of L. fasciata, in having a broad, dark-brown, midlateral stripe from the posterior rim of the orbit to the middle of the caudal-fin base. It is further distinguished from all other species in the genus by the combination of the following characters: premaxillae not in contact at symphysis, 16 precaudal vertebrae, minute tubercles scattered on the lower jaw, 28–33 lateral-line scales, 16–18 predorsal scales, 8½ branched dorsal-fin rays, 2½ scales between lateral line and pelvic-fin origin, and 16½–19½ branched anal-fin rays.